A Highly Expressed Human Protein, Apolipoprotein B-100, Serves as an Autoantigen in a Subgroup of Patients With Lyme Disease. (26th May 2015) - Crowley, Jameson T.; Drouin, Elise E.; Pianta, Annalisa; Strle, Klemen; Wang, Qi; Costello, Catherine E.; Steere, Allen C.
Abstract : To discover novel autoantigens associated with Lyme arthritis (LA), we identified T-cell epitopes presented in vivo by human leukocyte antigen (HLA)–DR molecules in patients' inflamed synovial tissue or joint fluid and tested each epitope for autoreactivity. Using this approach, we identified the highly expressed human protein, apolipoprotein B-100 (apoB-100), as a target of T- and B-cell responses in a subgroup of LA patients. Additionally, the joint fluid of these patients had markedly elevated levels of apoB-100 protein, which may contribute to its autoantigenicity. In patients with antibiotic-refractory LA, the magnitude of apoB-100 antibody responses correlated with increased numbers of plasma cells in synovial tissue, greater numbers and activation of endothelial cells, and more synovial fibroblast proliferation. Thus, a subset of LA patients have high levels of apoB-100 in their joints and autoreactive T- and B-cell responses to the protein, which likely contributes to pathogenic autoimmunity in patients with antibiotic-refractory LA.